Differentiated planetesimals record differing sources of sulfur in inner and outer solar system materials - Elizabeth A. Heiny; Edward M. Stolper; John M. Eiler (Proceedings of the National Academy of Sciences, 2025)
The isotope anomalies of noncarbonaceous (NC) and carbonaceous (CC) extraterrestrial materials provide a framework for tracing the distribution and accretion of matter in the early solar system. Here, we extend this framework to sulfur (S)—one of six “life-essential” volatile elements [T C ~ 664 K]—via the mass-independent S-isotope compositions of differentiated meteorites. We observe that on average, NC and CC iron meteorites are characterized by distinct Δ 33 S (Δ 33 S NC = 0.013 ± 0.003‰; Δ 33 S CC = −0.021 ± 0.009‰; 2 SE). The average Δ 36 S of NC and CC irons are less well resolved (Δ 36 S NC = −0.006 ± 0.039‰; Δ 36 S CC = −0.101 ± 0.114‰; 2 SE), but the Δ 36 S values of the CC irons are concentrated in the lower half of the range of those observed for iron meteorites. A lack of CC achondrite S-isotope analyses prevents direct comparison of the Δ 33 S and Δ 36 S of NC and CC achondrites, but the average Δ 33 S and Δ 36 S of NC achondrites (Δ 33 S = 0.02 ± 0.008; Δ 36 S = −0.019 ± 0.064‰; 2 SE) overlap with those of the NC irons. The average Δ 33 S values of NC achondrite groups also correlate with nucleosynthetic anomalies of other elements (e.g., Cr) previously used to define isotopic heterogeneity within the NC reservoir. The position of the Earth in Δ 33 S-Δ 36 S composition space implies that ~24% of terrestrial S derives from CC materials, while the majority (~76%) was delivered by NC materials.